Analisis Kekuatan Tarik Dan Foto Mikro Spesimen Serat Jagung Menggunakan Resin Lycal Dengan Variasi Metode Pembuatan Vacuum Infusion Dan Vacuum Bagging - Setiawan, Ferry; Dina Prasetia, Gilang; Suroso, Indreswari; Anhar, Muh (Indonesian Society of Applied Science, 2025)
Along with the development of drone technology, the development of technology in the field of materials also plays a role in advancing drone technology, where the use of materials for making drones must meet certain criteria. The natural fiber as a composite material used in this study is corn husk fiber. The type of matrix used in this study is lycal resin. And making it using the vacuum infusion and vacuum bagging methods. In addition, microstructure testing is carried out to determine the content of the content contained in the low-carbon steel specimen to be tested. By using a test specimen that has been refined so that the content in the test object can be seen. The method in this study was made of a specimen of corn fiber with lycal resin using the vacuum infusion and vacuum bagging methods, then it will be tested using tensile and microstructure tests. The results of the characteristics of the corn fiber composite material with the vacuum infusion manufacturing method, from the tensile test obtained an average value of 7.3 MPa, and in the microstructure test it can be seen that the fracture occurred due to air bubbles trapped in the specimen and the uneven weaving distance so that it affects the tensile strength. Characteristics of corn fiber composite material with vacuum bagging manufacturing method: from the tensile test results obtained an average value of 15.13 MPa, and in the microstructure test it can be seen that the fiber density level and the vacuum bagging method can produce higher specimen quality compared to vacuum infusion.